Mucoadhesive Buccal Tablets: Formulation Strategies, Evaluation Parameters, Marketed Products, and Future Prospects - Mankar D. Abhishek,; Dr. Vikrant P. Wankhade,; Ishika Bijore,; Saurabh Bodke,; Shrirang Virkhare., (Asian Journal of Pharmaceutical Research and Development, 2026)
Mucoadhesive buccal tablets are a promising and patient-friendly drug delivery system designed to improve the effectiveness of medications by enhancing bioavailability, avoiding first-pass metabolism, and providing a controlled release of drugs. The buccal route offers several benefits—it is easy to access, the mucosa is highly vascularized for quick absorption, and drugs can be protected from breakdown in the gastrointestinal tract. This review provides a clear overview of the basics of mucoadhesion, explaining how polymers interact with mucus and the factors that influence how strongly they adhere. Different types of mucoadhesive polymers—including natural, semi-synthetic, and synthetic varieties—are discussed with a focus on their properties and suitability for buccal formulations. The formulation aspects, such as how to choose the right drug, the importance of excipients, and the common methods used to prepare buccal tablets, are also highlighted. Key evaluation parameters like swelling index, mucoadhesive strength, and drug release patterns are explained to help understand how these systems are assessed. Recent developments—including advanced polymers, nanotechnology-based systems, and marketed products such as Fentora® and Belbuca®—show the growing clinical relevance of buccal mucoadhesive tablets. Although challenges remain, such as limited dose capacity and variations in mucosal conditions, ongoing innovations in thiolated polymers, interpenetrating polymer networks, and 3D-printing offer exciting potential to make these systems even more efficient and patient-friendly in the future.